Associations Between Self‐Reported Physical Activity and Physical Performance Measures Over Time in Postmenopausal Women: The Women's Health Initiative. Issue 10 (4th July 2017) - Laddu, Deepika R.; Wertheim, Betsy C.; Garcia, David O.; Brunner, Robert; Groessl, Erik; Shadyab, Aladdin H.; Going, Scott B.; LaMonte, Michael J.; Cannell, Brad; LeBoff, Meryl S.; Cauley, Jane A.; Thomson, Cynthia A.; et al.
Abstract : Objectives: To examine prospective associations between changes in physical activity (PA) and changes in physical performance measures (PPMs) over 6 years in older women. Design: Prospective cohort study. Setting: Forty clinical centers in the United States. Participants: Women aged 65 and older (mean age 69.8) enrolled in the Women's Health Initiative Clinical Trials with gait speed, timed chair stand, grip strength, and self‐reported recreational PA data assessed at baseline (1993–98) and follow‐up Years 1, 3, and 6 (N = 5, 092). Measurements: Mixed‐effects linear regression models were used to determine the association between time‐varying PA and change in each PPM. Potential interactions between time‐varying PA and age (<70, ≥70) were also tested. Results: Significan, dose‐response associations between PA and improvements in all PPMs were observed over the 6 years of follow‐up after adjusting for important covariates. High PA groups (≥1, 200 metabolic equivalent (MET)‐min/wk) had stronger grip strength (0.48 kg greater; P  < .01), more chair stands (0.35 more; P  < .001), and faster gait speeds (0.06 m/s faster; P  < .001) than sedentary women (<100 MET‐min/wk). Higher PA levels were associated with a greater increase in chair stands over time in women aged 70 and older ( P  < .001) than in those younger than 70 ( P interaction for age  = .01). Conclusion: In postmenopausal women, maintaining high PA levels over time is associated with better lower extremity function. These data support the view that regular PA plays an important role in maintaining functional status during aging in older women.